Prenatally diagnosed monochorionic diamniotic triplet pregnancy. Issue 8 (1st April 2015) - Yonetani, Naoto; Ishii, Keisuke; Mabuchi, Aki; Sasahara, Jun; Hayashi, Shusaku; Mitsuda, Nobuaki
Abstract We present an extremely rare case of monochorionic diamniotic (MD) triplet pregnancy diagnosed via ultrasonography at the end of the first trimester that resulted in delivery of three healthy newborns. Ultrasonography for a 34‐year‐old woman at 12 weeks of gestation showed three fetuses and one placenta with a T‐sign at the initial segment of the dividing membrane. Color Doppler examination revealed umbilical cord entanglement between two fetuses in one sac in addition to another sac containing one fetus. Therefore, this was diagnosed as MD triplet pregnancy. The triplets were delivered by cesarean section at 35 weeks of gestation and were healthy without neurological morbidities at the age of 28 days. Histopathological examination also revealed an MD triplet placenta. The possibility of MD triplet pregnancy should be recognized, although it is rare.